About unrealization of tungsten lines up to the ground state in the nonideal plasma of pulse discharges in water - Fedorovich, O.A. (Вопросы атомной науки и техники, 2009)
The paper considers the dynamics of tungsten impurity absorption line appearance in the plasma channel of the pulse
discharge in water (PDW) during the plasma relaxation process. In the initial stage of discharge (3 µs) any tungsten and
hydrogen absorption line is not observed in the spectrum. The optical gap width ∆Е in the nonideal plasma exceeds
5.5 eV. After 20 µs in the process of plasma relaxation, the absorption lines appear in the spectrum. They correspond to
transitions from the ground level to the levels with higher energies, not exceeding 3.24 eV, i.e. the gap width is 4.74 eV.
After 53 µs the gap width decreases down to 2.22 eV. The estimations of the electron concentration in the plasma,
obtained on the basis of the gap width, and on the plasma frequency, are in a good agreement. Розглянуто динаміку появи ліній поглинання вольфраму в неідеальній плазмі імпульсного розряду у воді
(ІРВ) при введені в канал домішок металу по мірі релаксації плазми. На початковій стадії розряду (3 мкс) в
спектрі не спостерігається ні одна лінія поглинання вольфраму і водню. Величина оптичної щілини ∆Е
перевищує 5.5 еВ. Через 20 мкс, по мірі релаксації плазми, з’являються спочатку лінії поглинання з переходами
з основного рівня на рівні з верхніми енергіями, які не перевищують 3.24 еВ, тобто з величиною щілини
4.74 еВ, і на 53 мкс величина щілини складає 2.22 еВ. Оцінки концентрації електронів в плазмі, зроблені за
величиною щілини і за плазмовою частотою, добре узгоджуються. Рассматривается динамика появления линий поглощения вольфрама в неидеальной плазме импульсного
разряда в воде (ИРВ) при введении в канал примесей метала по мере релаксации плазмы. На начальной стадии
разряда (3 мкс) в спектре не наблюдается ни одной линии поглощения вольфрама и водорода. Величина
оптической щели ∆Е превышает 5.5 эВ. Через 20 мкс, по мере релаксации плазмы, появляются вначале линии
поглощения с переходами с основного уровня на уровни с верхними энергиями, не превышающими 3.24 эВ, т.е.
с величиной щели 4.74 эВ, и на 53 микросекунде величина щели составляет 2.22 эВ. Оценки концентрации
электронов в плазме по величине щели и по плазменной частоте хорошо согласуются.